Innovative Noninvasive HPV Screening Using a Feminine Pad: A Pilot Study for Enhanced Cervical Cancer Detection - Rodrigo Aldariz-Amaya; Miriam Rodríguez-Esquivel; Alfonso Ruiz-Romero; Fernanda Anthor; Emmanuel Mares; Angélica Flores-Martínez; Edgar Alejandro Gómez-Villa; Marco Antonio Fuentes-Garcia; Teresa Apresa-García; Ricardo López-Romero; Emmanuel Salcedo; María de Jesús Nambo-Lucio; et al. (Obstetrics and Gynecology International)
Conclusions: The use of this noninvasive device demonstrated a significant correlation with clinical outcomes, supporting its potential as an effective and accessible tool for HPV screening. This method offers a promising alternative to conventional screening techniques, particularly in settings where traditional methods face logistical and socioeconomic challenges.